Low temperature resistant and high toughness asphalt pavement material
By using the branched structure of rigid main chains, flexible side chains and core-shell curing agents of organic acid anhydrides in epoxy asphalt materials, the problem of epoxy asphalt materials being prone to cracking under low temperature conditions is solved, and high toughness and good mechanical strength are achieved.
Patent Information
- Application Number
- CN202411250358.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-09-06
AI Technical Summary
Existing epoxy asphalt materials are prone to temperature stress under low temperature conditions, resulting in low temperature cracking, and when increasing toughness, they often damage their modulus and heat resistance.
The branched structure of rigid main chain and flexible side chain is used as the core structure, combined with organic acid anhydride as the shell structure, and the core-shell type curing agent is designed through open ring metathesis polymerization, which is well compatible with the epoxy resin to form a low-temperature resistant and high-toughness asphalt material.
Under low temperature conditions, the material has excellent toughness and good mechanical strength, which solves the problem of low-temperature cracking and maintains good heat resistance.
Smart Images

Figure CN119118570B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of asphalt materials, in particular to low-temperature-resistant and high-toughness asphalt pavement materials. Background Art
[0002] Asphalt materials are asphalt-based building materials that are widely used in the construction and maintenance of roads, airport runways, bridges and other infrastructure. Epoxy resins have excellent adhesion, chemical resistance and mechanical properties. Introducing them into asphalt systems can significantly improve the overall performance of the material.
[0003] Although epoxy asphalt has excellent performance, its own characteristics determine that it will become very brittle and hard after curing. At low temperatures, epoxy asphalt will produce large temperature stress, resulting in low-temperature cracking, which affects its performance. Generally speaking, adding active toughening agents that can react with epoxy resin or curing agent to the epoxy resin formula, such as rubber, thermoplastic resin, thermotropic liquid crystal polymer, interconductive network structure, core-shell polymer and nanoparticles, can improve the toughness of epoxy resin, but rubber toughening epoxy resin will greatly reduce the modulus and heat resistance of epoxy resin, and is not suitable for epoxy resin with high crosslinking degree; while thermoplastic resin will make the viscosity of the system too large, causing inconvenience in mixing, transportation and other links; although nanoparticle toughening can give epoxy resin higher physical and mechanical properties and heat resistance, nanoparticles have poor dispersibility in epoxy resin and are prone to agglomeration, which affects the toughening effect. Therefore, it is still necessary to develop a new epoxy resin asphalt that meets the requirements of low temperature resistance and high toughness. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention adopts a branched structure of a rigid main chain and a flexible side chain as the core structure, and an organic acid anhydride with a rigid structure as the shell structure, and synthesizes a curing agent with a core-shell structure through ring-opening metathesis polymerization. The curing agent has good compatibility with epoxy resin, and the epoxy resin asphalt material obtained by the curing agent has both excellent toughness and good mechanical strength under low temperature conditions.
[0005] The purpose of the present invention is to provide a low-temperature resistant and high-toughness asphalt pavement material, which comprises 200-250 parts of coarse aggregate, 650-750 parts of fine aggregate, 40-50 parts of mineral powder, and 45-70 parts of epoxy resin asphalt by weight; the epoxy resin asphalt comprises 45-50 parts of asphalt, 20-30 parts of epoxy resin, 20-30 parts of core-shell curing agent and 0.1-1 part of catalyst, and the preparation method of the core-shell curing agent is as follows: under a nitrogen atmosphere, 1-9 eq. A polyethylene glycol monomethyl ether-modified norbornene monomer, 1 eq of polyethylene glycol-modified norbornene monomer and 100 eq of solvent are freeze-thawed and degassed three times, and then the temperature is raised to 50-90° C., 0.04-0.2 eq of Grubbs catalyst is added to the mixture, and after stirring for 1-2 hours, 0.2-1 eq of nadic anhydride is added, and stirring is continued for 25-30 minutes. Ethyl vinyl ether is added to terminate the reaction, and excess solvent is removed by a rotary evaporator to obtain a core-shell curing agent.
[0006] Specifically, the preparation method of the polyethylene glycol monomethyl ether modified norbornene monomer is as follows: under a nitrogen atmosphere and at a temperature of 0 to 5° C., 1.2 to 1.5 eq of polyethylene glycol monomethyl ether, 30 eq of anhydrous dichloromethane, and 1.2 to 1.5 eq of triethylamine are added to a reaction kettle, 1 eq of 5-norbornene-2-yl chloride obtained in step S1 is dissolved in 5 eq of anhydrous dichloromethane and slowly added dropwise to the mixture, after reacting for 10 to 12 hours, the organic phase is washed with hydrochloric acid and sodium hydroxide solution respectively, the organic phase is collected, dried and filtered over anhydrous magnesium sulfate, and excess solvent is removed by a rotary evaporator to obtain the polyethylene glycol monomethyl ether modified norbornene monomer.
[0007] Specifically, the preparation method of the polyethylene glycol-modified norbornene monomer is as follows: under a nitrogen atmosphere and at a temperature of 0 to 5° C., 1.0 to 1.2 eq of polyethylene glycol, 30 eq of anhydrous dichloromethane, and 3.0 to 3.5 eq of triethylamine are added to a reaction kettle, 3 eq of 5-norbornene-2-yl chloride is dissolved in 5 eq of anhydrous dichloromethane and slowly added dropwise to the mixture, and after reacting for 14 to 16 hours, the organic phase is washed with hydrochloric acid and sodium hydroxide solution respectively, the organic phase is collected, dried and filtered with anhydrous magnesium sulfate, and the excess solvent is removed by a rotary evaporator to obtain the polyethylene glycol-modified norbornene monomer.
[0008] Specifically, the concentration of the sodium hydroxide and hydrochloric acid aqueous solutions is 1 to 2 mol / L.
[0009] Specifically, the preparation method of the 5-norbornene-2-yl chloride is as follows: under a nitrogen atmosphere, 1 eq of 5-norbornene-2-carboxylic acid and 8 to 10 eq of dichlorothionyl are added to a reaction kettle, stirred at a temperature of 70 to 80° C. for 1.5 to 3.0 hours, and the dichlorothionyl is evaporated to remove the dichlorothionyl without further purification to obtain 5-norbornene-2-yl chloride.
[0010] In the washing steps involved in the present invention, the volume ratio of the washing solvent to the washing liquid is 1:5.
[0011] Preferably, the amount of the polyethylene glycol monomethyl ether modified norbornene monomer added is 2 to 4 eq.
[0012] Preferably, the amount of nadic anhydride added is 0.4 to 0.8 eq.
[0013] Preferably, the epoxy resin main agent is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and aliphatic epoxy resin.
[0014] Bisphenol A epoxy resin has the widest application range among epoxy resins due to its advantages such as low price and small toxicity and side effects. More preferably, the main agent of the epoxy resin is bisphenol A epoxy resin.
[0015] Preferably, the catalyst is at least one of triethanolamine and diethanolamine.
[0016] Polyethylene glycol is a typical flexible chain segment. The longer the molecular chain, the better its flexibility. However, excessive flexibility will make the shape and position of the core easier to change, reducing the stability of the entire structure.
[0017] Preferably, the molecular weight of the polyethylene glycol monomethyl ether is 350 to 2000; more preferably, it is 800 to 1200.
[0018] Preferably, the molecular weight of the polyethylene glycol is 400-2000, more preferably 800-1200.
[0019] Preferably, the solvent is at least one of toluene and chloroform.
[0020] Preferably, the Grubbs catalyst is one or more of Grubbs first generation catalyst, Grubbs second generation catalyst and Grubbs third generation catalyst.
[0021] The molecular weight of the monomers polymerized in the core structure is relatively large, and a higher temperature is required for polymerization. Therefore, Grubbs' second-generation catalyst and Grubbs' third-generation catalyst with higher activity and stability are needed, but the price of Grubbs' third-generation catalyst is relatively high.
[0022] More preferably, the Grubbs catalyst is a second generation Grubbs catalyst.
[0023] Another object of the present invention is to provide a method for preparing a low temperature resistant and high toughness asphalt pavement material, comprising the following steps:
[0024] 1) Preparation of epoxy resin asphalt: heat the asphalt to 140-160°C, add epoxy resin preheated to 60-65°C, heat to 150-170°C and stir for 30-60 minutes, cool to 130-140°C, add core-shell curing agent and catalyst and stir thoroughly;
[0025] 2) Mixing and stirring: heat the coarse aggregate, fine aggregate and mineral powder to 160-180°C, remove moisture, grade and sieve according to design requirements, add the epoxy resin asphalt obtained in step 1) and stir at 160-180°C for 3-5 minutes to ensure uniform mixing;
[0026] 3) Spreading and curing: Use a paver to spread the mixture on the road surface, compact it with a roller, and then maintain it for 24 to 36 hours.
[0027] Preferably, the oil-to-stone ratio of the asphalt pavement material epoxy resin asphalt is 5% to 7%.
[0028] Beneficial Effects
[0029] The present invention has the following beneficial effects:
[0030] (1) The branched polymer core obtained by ring-opening metathesis polymerization can increase the cross-linking density between molecules. The rigid main chain provides overall stability, while the flexible side chain maintains a certain flexibility, which is conducive to absorbing and dispersing stress, thereby improving the toughness of the material; and the branched structure can form a semi-interpenetrating network, further increasing the deformation ability of the material.
[0031] (2) The outer layer of anhydride structure can not only react with epoxy resin as a curing agent, but also form some cross-linking points during the curing process to further enhance the network structure of the material.
[0032] (3) Since both the core and the shell contain structures that are compatible with the epoxy resin, the dispersibility and interfacial compatibility of the curing agent in the epoxy resin are improved, which is conducive to the toughening effect.
[0033] (4) It has a multi-scale toughening effect from the molecular level to the nanoscale, with the contribution of both flexible chain segments and the toughening effect of the nanophase.
[0034] The epoxy asphalt obtained by this curing agent not only has excellent toughness but also has good mechanical strength under low temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The schematic diagram of the synthesis route and inner and outer core structures of the core-shell curing agent of the present invention;
[0036] Figure 2 This is a transmission electron microscope image of the core-shell type 6 of the present invention. DETAILED DESCRIPTION
[0037] The following is a more detailed description of the specific implementation method of the present invention, the purpose of which is to explain the concept and characteristics of the present invention, and it cannot be used to limit the scope of protection of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.
[0038] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0039] The raw materials and equipment used in the embodiments and comparative examples are described as follows:
[0040] 5-Norbornene-2-carboxylic acid: product number N814812, purchased from Shanghai MacLean Biochemical;
[0041] Thionyl chloride: product number T819486, purchased from Shanghai MacLean Biochemical;
[0042] Nadic anhydride: product number N814504, purchased from Shanghai MacLean Biochemical;
[0043] Grubbs II catalyst: product number D828408, purchased from Shanghai MacLean Biochemical;
[0044] Bisphenol A epoxy resin: Product No. XHL1920, purchased from Hubei Xinhongli Chemical Co., Ltd.;
[0045] Polyethylene glycol monomethyl ether 1: average molecular weight 350, purchased from Tianjin Xiensi Biochemical Technology;
[0046] Polyethylene glycol monomethyl ether 2: average molecular weight 1000, purchased from Tianjin Xiensi Biochemical Technology;
[0047] Polyethylene glycol monomethyl ether 3: average molecular weight 2000, purchased from Tianjin Xiensi Biochemical Technology;
[0048] Polyethylene glycol 1: average molecular weight 400, purchased from Shanghai Aladdin Biochemical Technology;
[0049] Polyethylene glycol 2: average molecular weight 1000, purchased from Shanghai Aladdin Biochemical Technology;
[0050] Polyethylene glycol 3: average molecular weight 2000, purchased from Shanghai Aladdin Biochemical Technology;
[0051] 5-Norbornene-2-yl chloride: Under nitrogen atmosphere, add 1 eq of 5-norbornene-2-carboxylic acid and 10 eq of thionyl chloride to a reaction kettle, stir at 80°C for 2.0 h, evaporate the thionyl chloride, and obtain 5-norbornene-2-yl chloride without further purification;
[0052] Aggregate: It is composed of coarse aggregate (diabase), fine aggregate (Qingyuan river sand) and mineral powder (purchased from Huzhou Lanyun Ore Powder Co., Ltd.) sieved and graded. The gradation composition of the aggregate is shown in Table 1;
[0053] Asphalt: It meets the index requirements of "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004), and the asphalt is No. 70 heavy traffic asphalt.
[0054] Table 1 Aggregate gradation composition
[0055]
[0056] The following is the test method of the performance parameters involved in the present invention:
[0057] Flexural strength and maximum flexural strain: The asphalt pavement material is cut into prismatic beams with a length of 250 mm, a width of 30 mm, and a height of 35 mm. The span is 200 mm. The test adopts a midpoint loading rate of 50 mm / min.
[0058] Formula 1,
[0059] Formula 2,
[0060] R β : flexural tensile strength of the specimen when it is destroyed (Mpa), F0: the failure load of the specimen when it is destroyed (N), L, b, h: the span of the specimen, the width and height of the cross section in the span (mm),
[0061] ε B : maximum bending-tensile strain, d: mid-span deflection when the specimen fails (mm);
[0062] Marshall test stability: Prepare and measure the specimens according to "JTJ 052-2000 Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".
[0063] Polyethylene glycol monomethyl ether modified norbornene monomer 1
[0064] Under nitrogen atmosphere and at a temperature of 0°C, 1.5 eq of polyethylene glycol monomethyl ether 1, 30 eq of anhydrous dichloromethane and 1.5 eq of triethylamine were added to a reaction kettle, 5-norbornene-2-yl chloride was dissolved in 5 eq of anhydrous dichloromethane and slowly added dropwise to the mixture. After reacting for 12 h, the organic phase was washed with hydrochloric acid and sodium hydroxide solution respectively, the organic phase was collected, dried over anhydrous magnesium sulfate and filtered, and the excess solvent was removed by a rotary evaporator to obtain polyethylene glycol monomethyl ether modified norbornene monomer 1;
[0065] Polyethylene glycol monomethyl ether modified norbornene monomer 2
[0066] Compared with the preparation method of polyethylene glycol monomethyl ether-modified norbornene monomer 1, the difference lies in that polyethylene glycol monomethyl ether 1 is replaced by polyethylene glycol monomethyl ether 2.
[0067] Polyethylene glycol monomethyl ether modified norbornene monomer 3
[0068] Compared with the preparation method of polyethylene glycol monomethyl ether-modified norbornene monomer 1, the difference lies in that polyethylene glycol monomethyl ether 1 is replaced by polyethylene glycol monomethyl ether 3.
[0069] Polyethylene glycol-modified norbornene monomer 1
[0070] Under nitrogen atmosphere and at a temperature of 0°C, 1.2 eq of polyethylene glycol 1, 30 eq of anhydrous dichloromethane, and 3.0 eq of triethylamine were added to a reaction kettle, 3 eq of 5-norbornene-2-yl chloride was dissolved in 5 eq of anhydrous dichloromethane and slowly added dropwise to the mixture. After reacting for 16 h, the organic phase was washed with hydrochloric acid and sodium hydroxide solution respectively, the organic phase was collected, dried over anhydrous magnesium sulfate, filtered, and the excess solvent was removed by a rotary evaporator to obtain polyethylene glycol-modified norbornene monomer 1;
[0071] Polyethylene glycol-modified norbornene monomer 2
[0072] Compared with the preparation method of polyethylene glycol-modified norbornene monomer 1, the difference is that polyethylene glycol 1 is replaced by polyethylene glycol 2.
[0073] Polyethylene glycol-modified norbornene monomer 3
[0074] Compared with the preparation method of polyethylene glycol-modified norbornene monomer 1, the difference is that polyethylene glycol 1 is replaced by polyethylene glycol 3.
[0075] Core-shell curing agent 1~6
[0076] Under nitrogen atmosphere, 1-9 eq polyethylene glycol monomethyl ether modified norbornene monomer, 1 eq polyethylene glycol modified norbornene monomer and 100 eq toluene were added to a Shrek bottle. After freeze-thaw degassing three times, the temperature was raised to 90°C, 0.04-0.2 eq Grubbs catalyst was added to the mixture, and after stirring for 2 h, 0.2-1 eq norbornene anhydride was added, and stirring was continued for 30 min. Ethyl vinyl ether was added to terminate the reaction, and excess solvent was removed by rotary evaporator to obtain a core-shell curing agent.
[0077] Depend on Figure 2 It can be seen that the particle size of the obtained core-shell type curing agent 6 is 180-200 nm, which is a nanostructure.
[0078] Table 2 Preparation ratio of core-shell curing agent 1 to 6 (eq)
[0079]
[0080]
[0081] Comparison of curing agent 1
[0082] 3 eq polyethylene glycol monomethyl ether modified norbornene monomer 1, 1 eq polyethylene glycol modified norbornene monomer 1 and 0.4 eq norbornene diacid anhydride were physically blended as comparative curing agent 2.
[0083] Comparison of curing agent 2
[0084] A linear copolymer was obtained as a comparative curing agent 2 by copolymerizing 4 eq polyethylene glycol monomethyl ether-modified norbornene monomer 1 with 0.4 eq norbornene anhydride.
[0085] Examples 1 to 6
[0086] 1) Preparation of epoxy resin asphalt: heat the asphalt to 140°C, add bisphenol A epoxy resin preheated to 65°C, heat to 160°C and stir for 50 minutes, cool to 130-140°C, add core-shell curing agent and diethanolamine and stir thoroughly;
[0087] 2) Mixing and stirring: heat 1000 parts by weight of coarse aggregate, fine aggregate and mineral powder to 160° C., remove moisture, grade and sieve according to design requirements, add 55 parts by weight of epoxy resin asphalt obtained in step 1) and stir at 180° C. for 3 minutes to ensure uniform mixing. The formula of the epoxy resin asphalt is shown in Table 3;
[0088] 3) Spreading and curing: Use a paver to spread the mixture on the road surface, compact it with a roller, and then maintain for 24 hours.
[0089] Table 3 Formula of epoxy resin asphalt material (parts by weight)
[0090]
[0091]
[0092] Table 4 Performance data of low temperature resistant and high toughness asphalt pavement materials
[0093]
[0094] It can be seen from the data in Table 3 that the epoxy asphalt obtained by the curing agent not only has excellent toughness but also has good mechanical strength under low temperature and room temperature conditions.
[0095] From the data of Examples 1, 2, and 3 in Table 3, it can be seen that the more the proportion of the core bifunctional molecules is, the higher the branching degree is, the greater the bending tensile strength and the stability of the Marshall test will be after curing, and the maximum bending tensile strain will be reduced; from the data of Examples 3 and 4, it can be seen that the greater the proportion of the cured molecules in the outer layer structure, the higher the crosslinking density after curing, the greater the bending tensile strength and the stability of the Marshall test will be, and the maximum bending tensile strain will be reduced. From the data of Examples 4, 5, and 6, it can be seen that the soft chain molecular weight in the inner layer molecules increases, and the bending tensile strength and the stability of the Marshall test are reduced after curing, and the maximum bending tensile strain increases; from the data of Comparative Example 1 and Example 4, it can be seen that the comparison curing agent 1 obtained after adding physical blending can only improve the bending tensile strength, and the maximum bending tensile strain is reduced a lot; from the data of Comparative Example 2 and Example 4, it can be seen that the comparison curing agent 2 obtained by adding linear copolymerization can improve a certain bending tensile strength and the maximum bending tensile strain, but the effect is poor.
[0096] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Low temperature resistant and high toughness asphalt pavement material, characterized in that: The invention comprises 200-250 parts of coarse aggregate, 650-750 parts of fine aggregate, 40-50 parts of mineral powder and 45-70 parts of epoxy resin asphalt by weight; the epoxy resin asphalt comprises 45-50 parts of asphalt, 20-30 parts of epoxy resin, 20-30 parts of core-shell curing agent and 0.1-1 part of catalyst. The preparation method of the core-shell curing agent is as follows: under nitrogen atmosphere, 1-9 eq polyethylene glycol monomethyl ether modified norbornene monomer, 1 eq polyethylene glycol modified norbornene monomer and 100 eq solvent are added, after freeze-thaw degassing three times, the temperature is increased to 50-90° C., 0.04-0.2 eq of Grubbs catalyst is added to the mixture, after stirring for 1-2 hours, 0.2-1 eq of norbornene anhydride is added, stirring is continued for 25-30 minutes, vinyl ethyl ether is added to terminate the reaction, and excess solvent is removed by rotary evaporator to obtain the core-shell curing agent.
2. The low temperature resistant and high toughness asphalt pavement material according to claim 1, characterized in that: The preparation method of the polyethylene glycol monomethyl ether modified norbornene monomer is as follows: under a nitrogen atmosphere and at a temperature of 0 to 5° C., 1.2 to 1.5 eq of polyethylene glycol monomethyl ether, 30 eq of anhydrous dichloromethane, and 1.2 to 1.5 eq of triethylamine are added to a reaction kettle, 1 eq of 5-norbornene-2-yl chloride is dissolved in 5 eq of anhydrous dichloromethane and slowly added dropwise to the mixture, after reacting for 10 to 12 hours, the organic phase is washed with hydrochloric acid and sodium hydroxide solution respectively, the organic phase is collected, dried and filtered with anhydrous magnesium sulfate, and the excess solvent is removed by a rotary evaporator to obtain the polyethylene glycol monomethyl ether modified norbornene monomer.
3. The low temperature resistant and high toughness asphalt pavement material according to claim 1, characterized in that: The preparation method of the polyethylene glycol-modified norbornene monomer is as follows: under a nitrogen atmosphere and at a temperature of 0 to 5° C., 1.0 to 1.2 eq of polyethylene glycol, 30 eq of anhydrous dichloromethane, and 3.0 to 3.5 eq of triethylamine are added to a reaction kettle, 3 eq of 5-norbornene-2-yl chloride is dissolved in 5 eq of anhydrous dichloromethane and slowly added dropwise to the mixture, after reacting for 14 to 16 hours, the organic phase is washed with hydrochloric acid and sodium hydroxide solution respectively, the organic phase is collected, dried and filtered with anhydrous magnesium sulfate, and the excess solvent is removed by a rotary evaporator to obtain the polyethylene glycol-modified norbornene monomer.
4. The low temperature resistant and high toughness asphalt pavement material according to claim 1, characterized in that: The epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and aliphatic epoxy resin.
5. The low temperature resistant and high toughness asphalt pavement material according to claim 1, characterized in that: The catalyst is at least one of triethanolamine and diethanolamine.
6. The low temperature resistant and high toughness asphalt pavement material according to claim 2, characterized in that: The molecular weight of the polyethylene glycol monomethyl ether is 350-2000.
7. The low temperature resistant and high toughness asphalt pavement material according to claim 3, characterized in that: The molecular weight of the polyethylene glycol is 400-2000.
8. The low temperature resistant and high toughness asphalt pavement material according to claim 1, characterized in that: The solvent is at least one of toluene and chloroform.
9. The low temperature resistant and high toughness asphalt pavement material according to claim 1, characterized in that: The Grubbs catalyst is one or more of a Grubbs first generation catalyst, a Grubbs second generation catalyst and a Grubbs third generation catalyst.
10. The method for preparing the low temperature resistant and high toughness asphalt pavement material according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Preparation of epoxy resin asphalt: heat the asphalt to 140-160°C, add epoxy resin preheated to 60-65°C, heat to 150-170°C and stir for 30-60 minutes, cool to 130-140°C, add core-shell curing agent and catalyst and stir thoroughly; 2) Mixing and stirring: heat the coarse aggregate, fine aggregate and mineral powder to 160-180°C, remove moisture, grade and sieve according to design requirements, add the epoxy resin asphalt obtained in step 1) and stir at 160-180°C for 3-5 minutes; 3) Spreading and curing: Use a paver to spread the mixture on the road surface, compact it with a roller, and then maintain it for 24 to 36 hours.
Citation Information
Patent Citations
High-modulus asphalt material with excellent durability and preparation method thereof
CN112574583A
High-temperature secondary curing epoxy modified asphalt pavement paving material and preparation and use method thereof
CN112724698A